THE EFFECT OF USING BLOGGER ON STUDENTS’ ACHIEVEMENT IN WRITING RECOUNT TEXT - Aprida, Nurul; Rahmawati, Wiki Tedi; Zulkarnain, Iskandar (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The objective of this research was to determine whether there is a significant effect of using Blogger on students' achievement in writing recount text. This study was conducted using an experimental research design with two groups. The population in this research was all the 8th grade students of SMP Taman Siswa Tanjung Sari Medan. There were two parallel classes namely 8-1 and 8-2, each class consisted of 30 students and the total of samples was 60 students. The sampling technique used was cluster random sampling with Lottery Technique. Class 8-1 was selected as the experimental group and class 8-2 was selected as the control group. The experimental group was taught using Blogger while the control group was taught using paper based. The instrument used in this research was a writing test consisting of pre-test and post-test. The data were analyzed using t-test. The results showed that the t_count value was greater than the t_table value (2.50 > 2.00) with the degree of freedom (df) = 58 at the significance level α = 0.05. This means that the Alternative Hypothesis (Ha) was successfully accepted and the Null Hypothesis (Ho) was successfully rejected. Therefore it can be concluded that the using Blogger has a significant effect on students' achievement in writing recount text.